Federal System in Nepal: Principles and Constitutional Arrangements - Shrestha, Milan (Janabhawana Research Journal, 2025)
Nepal has been practicing federal system under the new constitution proclaimed through the Constituent Assembly (CA). Theoretically, federal system is a form of government in which the state powers are not only separated horizontally (legislative, executive, and judiciary), but also distributed vertically among the levels of government (centre and political constituents). As a system of government, federalism is guided by certain principles under which legal authorities are distributed, competent institutions are designed, the capacity of the institutions is enhanced, and prompt services are delivered. The basic objective of the federal system in Nepal is to end exploitation, discrimination, and alienation based on class, ethnicity, caste, and region. Scrutinizing legal texts and related literatures, this article discusses the principle of federalism, constitutional and legal arrangements, and their operation to make the federal system in a real sense. This article also identifies provisional gaps (both constitutional and legal) to make the system more effective and meaningful. It highlights key issues to be addressed for maintaining some degree of autonomy, competencies, and genuine results to make the federal system more successful, also at the operational level.